2003
DOI: 10.1007/s00039-003-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

Finite jet determination of local analytic CR automorphisms and their parametrization by 2-jets in the finite type case

Abstract: We show that germs of local real-analytic CR automorphisms of a real-analytic hypersurface M in C 2 at a point p ∈ M are uniquely determined by their jets of some finite order at p if and only if M is not Levi-flat near p. This seems to be the first necessary and sufficient result on finite jet determination and the first result of this kind in the infinite type case.If M is of finite type at p, we prove a stronger assertion: the local real-analytic CR automorphisms of M fixing p are analytically parametrized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…For a hypersurface in C 2 Ebenfelt, Lamel & Zaitsev [ELZ01] have recently found optimal results for finite determination of biholomorphisms. …”
Section: Finite Determination Of Mappings: Results and Conjecturesmentioning
confidence: 99%
“…For a hypersurface in C 2 Ebenfelt, Lamel & Zaitsev [ELZ01] have recently found optimal results for finite determination of biholomorphisms. …”
Section: Finite Determination Of Mappings: Results and Conjecturesmentioning
confidence: 99%
“…(For more information, see the survey articles [BER00] and [Vit90].) More recently, Ebenfelt, Lamel, and Zaitsev [ELZ00] have shown that the stability group of any hypersurface of finite type in C 2 is determined by 2-jets.…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…Hence, the stability groups of hypersurfaces of infinite type need not be determined by 2-jets. However, in [ELZ00] it is shown that the stability group of any nonflat realanalytic hypersurface is determined by jets of some predetermined finite order. For the special case of so-called 1-infinite type hypersurfaces, of which M is an example, the author has shown [Kow01] that the stability group is in fact formally parametrized by such a finite jet.…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…These results have been extended more recently to ever more general hypersurfaces. For example, Ebenfelt, Lamel, and Zaitsev [5] proved the stability group of any Levi nonflat hypersurface (M, p) in C 2 is determined by k-jets for some finite number k; moreover, if M is of finite type at p (i.e. contains no complex hypersurface passing through p), then 2-jets will always suffice.…”
Section: Introductionmentioning
confidence: 99%